A Dimensional Splitting of ETD Schemes for Reaction-Diffusion Systems. (17th May 2016) - Asante-Asamani, E. O.; Wade, Bruce A.
Abstract: Novel dimensional splitting techniques are developed for ETD Schemes which are second-order convergent and highly efficient. By using the ETD-Crank-Nicolson scheme we show that the proposed techniques can reduce the computational time for nonlinear reaction-diffusion systems by up to 70%. Numerical tests are performed to empirically validate the superior performance of the splitting methods.